Neutrophil Lymphocyte Ratio as a Predictor of Chronic Low Back Pain Severity - Setiani, Putu; Dwi Sihanto, Rindha; Ngurah Purna Putra, I Gusti; Ngurah Angga Nugraha, I Gusti; Ayu Meilinda Dusak, Kadek; Ayu Savitri Mahadewi, Kadek (Jurnal Health Sains, 2025)
Low back pain is a frequently seen problem in the society and causes loss of productivity. In recent studies, inflammatory mediators and inflammation itself has an efficient role in pain mechanism. We aimed to investigate the association between the neutrophil to lymphocyte ratio level as an inflammatory biomarker with pain severity patients with chronic low back pain. A retrospective analysis was conducted on medical records of low back pain patients between Januari until December 2024 in Neurology Department of Bhakti Rahayu Denpasar Hospital. Seventy-three medical record patients between 27-81 years old were included in the study. The neutrophil-to-lymphocyte ratio (NLR) is calculated by dividing the absolute neutrophil count by the absolute lymphocyte count based on blood samples. The patients were divided into two groups based on pain severity. The average age of the participants was 56,63 years (±15,56) (p= 0,077), with 40 males (54,85) and 33 females (45,2%) with average neutrophil count 5,99 x 109/L (±1,45) (p= 0,200) and lymphocyte count 1,75x 109/L (±0,39) (p= 0,093). NLR cut-off was 3,55 (±0,72) (p= 0,200). Higher NLR correlated with age (r = 0.243, p = 0.038) and pain score (r = 0.394 p < 0.001). High NLR increased the risk of 33, 43 LBP patients experiencing moderate pain (p= <0.001). NLR may be used as a simple and reliable premise independent predictor of pain severity in patients with chronic low back pain